2017
DOI: 10.1002/jcc.24828
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of Hartree-Fock exchange, correlation energy and long range corrections in evaluating ionization potential, and electron affinity in density functional theory

Abstract: Accurate determination of ionization potentials (IPs), electron affinities (EAs), fundamental gaps (FGs), and HOMO, LUMO energy levels of organic molecules play an important role in modeling and predicting the efficiencies of organic photovoltaics, OLEDs etc. In this work, we investigate the effects of Hartree Fock (HF) Exchange, correlation energy, and long range corrections in predicting IP and EA in Hybrid Functionals. We observe increase in percentage of HF exchange results in increase of IPs and decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Hybrid functionals generally outperform pure density functionals (e.g., those based on the local density approximation and generalized gradient approximations [GGAs]) in evaluating IPs, EAs, and FGs . Our recent investigations concluded that among the various types of XC functionals available (e.g., global hybrid, long‐range corrected (LC) hybrid, and double‐hybrid functionals), the performance of LC hybrid functionals is superior and consistent for the IPs, EAs, and FGs of neutral molecules . Similar conclusions were also made in earlier studies .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Hybrid functionals generally outperform pure density functionals (e.g., those based on the local density approximation and generalized gradient approximations [GGAs]) in evaluating IPs, EAs, and FGs . Our recent investigations concluded that among the various types of XC functionals available (e.g., global hybrid, long‐range corrected (LC) hybrid, and double‐hybrid functionals), the performance of LC hybrid functionals is superior and consistent for the IPs, EAs, and FGs of neutral molecules . Similar conclusions were also made in earlier studies .…”
Section: Introductionsupporting
confidence: 83%
“…These materials are gradually replacing the traditional materials (e.g., their inorganic counterparts) in different fields that have been dominating the markets over the past few decades. The function and performance of these materials depends heavily on their optoelectronic properties, including the vertical ionization potentials (IPs), vertical electron affinities (EAs), fundamental gaps (FGs), optical gaps, and so forth . For example, organic light emitting diodes contain several layers of different stacked organic films, and there exists an energy barrier to the flow of charge between these layers, therefore, the knowledge of transport energy levels is required along with IPs, EAs, and FGs that can help in optimizing and designing the devices with higher efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain quantitatively accurate results for benchmarking the DFT methods, torsional energies are evaluated employing CCSD/ATZ with the optimized geometries of CCSD/ADZ at 90 0 , 0 0 , and 180 0 , respectively. (Note: the dihedral angle of dimer is fixed and the remaining geometry is allowed to optimize with CCSD/ADZ @ 0 0 , 90 0 , and 180 0 ) Larger basis set ATZ with CCSD provides accurate relative energies, which are closer to the complete basis set limit . Torsional energy barriers employing CCSD/ADZ vary from CCSD/ATZ (Supporting Information Tables S1, S2, S3, and S4).…”
Section: Resultsmentioning
confidence: 99%
“…(Note: the dihedral angle of dimer is fixed and the remaining geometry is allowed to optimize with CCSD/ADZ @ 0 0 , 90 0 , and 180 0 ) Larger basis set ATZ with CCSD provides accurate relative energies, which are closer to the complete basis set limit. [31] Torsional energy barriers employing CCSD/ADZ vary from CCSD/ATZ (Supporting Information Tables S1, S2, S3, and S4). Ab-initio methods are relatively more sensitive to the basis set compared to DFT methods (≤0.13 kcal/mol on dimeric systems).…”
Section: Resultsmentioning
confidence: 99%